VISHNU IN TWO CLASSICAL JAVANESE ISLAMIC TEXTS: Continuity and Harmony among the Javanese Revisited (JOURNAL OF INDONESIAN ISLAM, 2023)
This paper discusses the character of Wisnu (Vishnu) in Javanese culture as seen from two classical Javanese Islamic texts, namely Babad Tanah Jawi and Serat Suluk Warna-warni. Based on the two texts, this paper argues that Vishnu has been historically inseparable from the development of Islam in Java. Called the first king in the Land of Java, Vishnu was seen as the progenitor for the hereditary rulers of Java up to the Kingdom of Mataram Islam. In the texts, Vishnu underwent a transformation from one of the major deities in Hinduism to an important figure in the development of Islam in Java. Vishnu's reincarnation is also present in the form of artifacts and various wayang (shadow puppet) plays. In the context of Java, Vishnu and Islam represent a form of continuity that emphasizes the importance of the harmony of the universe. The presence of Vishnu and Islam brought safety and peace into the life of the Javanese. This study is expected to inspire the idea that revisiting literary works of the past could contribute to efforts to develop a peaceful and harmonious cultural life in Java.